2022
DOI: 10.1007/s00167-022-07161-6
|View full text |Cite
|
Sign up to set email alerts
|

Intrameniscal degeneration and meniscotibial ligament loosening are associated factors with meniscal extrusion of symptomatic discoid lateral meniscus

Abstract: Purpose This study aimed to compare the amount of extrusion of the discoid lateral meniscus (DLM), which was symptomatic and required surgery, with normal meniscuses and asymptomatic DLMs and examine factors associated with the extrusion of symptomatic DLM. Methods Medical records of participants with DLM or normal lateral meniscus (LM) were retrospectively reviewed using magnetic resonance imaging (MRI). DLM cases were divided into symptomatic and asymptomatic groups. The midbody meniscal extrusion was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Meniscal extrusion was slightly greater in the symptomatic than in the asymptomatic group. Previous studies have shown that meniscal extrusion is more frequent in symptomatic DLMs than in asymptomatic DLMs or normal menisci [11] and that the extent of extrusion progresses after saucerization with or without repair [12,21], which is consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Meniscal extrusion was slightly greater in the symptomatic than in the asymptomatic group. Previous studies have shown that meniscal extrusion is more frequent in symptomatic DLMs than in asymptomatic DLMs or normal menisci [11] and that the extent of extrusion progresses after saucerization with or without repair [12,21], which is consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 93%
“…The symptomatic group was further subdivided according to whether there was an intrameniscal high signal indicating a horizontal tear on MRI fat saturation scans. [11, 23]. The group without a horizontal tear was referred to as group “N” and the group with a horizontal tear was referred to as group “H”.…”
Section: Methodsmentioning
confidence: 99%
“…El menisco discoide es una variante morfológica, descrita por primera vez en 1889, que condiciona una alteración de la cinemática de la rodilla con un aumento de la incidencia de desgarros e inestabilidad del menisco a una temprana edad. A nivel mundial su prevalencia se calcula en 5.0-16.6%, siendo aparentemente más prevalente en la población asiática 1 ; sin embargo, al ser una entidad principalmente asintomática está prevalencia pudiera estar infraestimada. Si bien sus complicaciones son bien conocidas, su etiopatogenia, clasificación y tratamiento siguen siendo discutidos.…”
Section: Introductionunclassified
“…17,27 Meniscal extrusion is associated with various pathologies (eg, early knee osteoarthrosis, meniscus posterior root tears, radial tears) after anterior cruciate ligament reconstruction 28 and after meniscectomy for symptomatic discoid lateral meniscus. 3,14,23 It is frequently accompanied by rapid progression of the degenerative process of the knee as well as by substantial morbidity and pain. 14 Restoring the lost function caused by meniscal extrusion can delay osteoarthrosis progression 25 and/or lead to improvement of articular cartilage after a meniscal allograft transplantation.…”
mentioning
confidence: 99%